Adult attachment and trait anxiety among Chinese college students: A multiple mediation model - Xu Li; Peizhen Sun; Li Li (Frontiers in Public Health, 2022)
The present study discusses the relationship between adult attachment and trait anxiety of Chinese college students based on the “internal working models” theory. Six hundred and seventy-two valid data were collected using a self-reported questionnaire. The mediating roles of self-esteem, perceived social support, and security in the relationship between adult attachment orientations (anxiety and avoidance) and trait anxiety were investigated using the structural equation model and bootstrap methods. The results showed that: self-esteem and security play mediating roles in the relationship between attachment anxiety and trait anxiety. self-esteem, perceived social support, and security play mediating roles in the relationship between attachment avoidance and trait anxiety. In addition, there were different mediation mechanisms in the correlation between different attachment dimensions and trait anxiety. This study provided empirical data for exploring the formation and maintenance of trait anxiety in college students and had a specific significance for the early prevention and clinical intervention of anxiety-related disorders.